Spatial design framework of Islamic boarding schools in West Java, Indonesia - Rangga, Firmansyah (2023)
Islamic boarding schools, also known as Pondok Pesantren, play a significant role in Indonesia's educational system. This indicates that their relevance is expanding in tandem with the rise in the number of educational institutions and the number of students. When it comes to the formation and development of contemporary Islamic boarding schools in Indonesia, a country that is defined by its predominantly Muslim population, this research fills a significant need in the regulatory frameworks and academic investigation that have been available up until now. A mixed-method approach is utilized in this investigation, which falls under the category of case study research. The study focuses on five contemporary Islamic boarding schools located throughout West Java, Indonesia. A design framework that is adapted to the modern Islamic boarding school context in the West Java area is proposed as the result of this study. The framework emphasizes four crucial areas, namely learning models and spaces, internal dynamics, Islamic principles, and expert inputs. It takes into account the requirement for a holistic design approach that takes into account factors such as location, facility development, support infrastructure, aspects of the locality, environmental responsiveness, and adherence to Islamic ideals such as comfort, cleanliness, accessibility, and aesthetics, among other things. By giving a focused examination of contemporary Islamic boarding schools, this research not only fills a substantial gap in the existing literature but also establishes a precedent for future architectural and pedagogical development within the framework of Islam in Indonesia.